Rancang Bangun Sistem Informasi Rekomendasi Berita dan Pembelajaran Budaya di Indonesia Menggunakan Metode Simple Weighted Average (SWA) - Jackri Hendrik; Leony Hoki (STMIK Budi Darma, 2022)
Culture is a pattern or way of life that continues to develop by a group of people and is passed down to the next generation. A culture is usually passed down from generation to generation to their children and grandchildren with the aim that the culture will still exist and be known by the heirs. In practice, introducing the culture/customs of an area is usually done manually, that is, where the advice will convey cultural information to their children and grandchildren. This manual process is certainly not very effective and efficient because it has a very small range of information so it is difficult to introduce cultural information to all regions in Indonesia. In addition to manually, to obtain cultural information in Indonesia can also be done via the internet such as through the Google website or other applications. However, the drawbacks of existing websites and applications are that they only provide news and cultural information in Indonesia at this time and there is no use of intelligent systems in them such as recommendation systems. Therefore, a research will be conducted to design a website information system for news recommendations and cultural learning by applying the Simple Weighted Average method. The results showed that the application of the Simple Weighted Average method proved to be quite accurate in providing recommendations for news and cultural learning in Indonesia because it was based on rating patterns from other users.